Finite element analysis of stress extent at peri-implant bone surrounding external hexagon or Morse taper implants. (July 2017) - Macedo, J.P.; Pereira, J.; Faria, J.; Pereira, C.A.; Alves, J.L.; Henriques, B.; Souza, J.C.M.; López-López, J.
Abstract: Purpose: The purpose of the present study was to evaluate the distribution of stresses and consequent bone volume affected surrounding external hexagon or Morse taper dental implant systems by finite element analysis. Material and methods: Two different dental implant-abutment designs were assessed: external hexagon or Morse taper joints. A mandibular bone model obtained from a computed tomography scan was used. The implant-abutment systems were axially or obliquely (45°) loaded on 150 N relatively to the central axis of the implant. The von Mises stresses were analysed in terms of magnitude and volume of affected surrounding bone. Results: The von Mises equivalent values found on the cortical bone were higher than that recorded on the trabecular bone. Additionally, the bone volume associated with high stress values was higher in cortical and trabecular bone for oblique loading compared to axial loading. The values of von Mises equivalent stress around Morse taper implant-abutment system were lower on both axial and oblique loads than those recorded for external hexagon implant-abutment systems. Conclusions: Morse taper implant joints revealed a proper biomechanical behavior when compared to external hexagon systems concerning a significant volume of surrounding peri-implant bone subjected to lower stresses values.